FACTORS FOR SMALLHOLDERS PERSISTENCE IN RURAL MALAYSIA: EVIDENCE FROM RICE FARMING COMMUNITY IN SELANGOR STATE - Khairul Hisyam KAMARUDIN; Mohamad Fadhli RASHID (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper examines the factors of smallholders’ persistence in the rural area of Malaysia based on a case study of rice farming community in Parit 6 (East) village in the state of Selangor, Malaysia. Information for this paper are derived from in-depth interviews with key informants and series of field observation conducted in July and August 2017. The findings from the fieldwork highlights four major factors for smallholders’ persistence which are strongly associated with strong and influential internal and external support systems including; (1) strong engagement and supports from various government agencies which include systematic distribution of subsidy and development grants, and development of irrigation infrastructure, (2) legality of land ownership, (3) farmers’ ability in utilizing capital to expand local economic and improve quality of life and, (4) diversification of economic activities through farming and non-farming projects. The paper could offer valuable insights particularly in understanding some of the underlying factors for smallholders’ persistence and sustainability particularly in the case of rice farming community in rural areas.